The Implications of the Bai’at of the Sammaniyah Tarekat on the Competence of Educators, in Jambi, Indonesia - Usman, Usman; Usman, A’zhami Alim; Zaman, Arpan (Islamika : Jurnal Ilmu-Ilmu Keislaman, 2024)
This study aims to explore the process of Bai’at of educators in the Sammaniyah Tariqah and its implications for changes in educator competence in Jambi Province, Indonesia. This study used a qualitative approach with phenomenological methods. The research participants consisted of four educators who had participated in the Bai’at process of Sammaniyah Tariqah. Data were collected through semi-structured and unstructured interviews. Data analysis was conducted using a thematic analysis approach that refers to Braun and Clarke's theory through six steps: data coding, theme identification, review, theme naming, and reporting. The results show that the Bai’at process involves two main stages: first, the process of commitment or agreement made by the educator to carry out his duties and responsibilities with full seriousness, covering aspects of ethics, morals, and dzikr practice according to the stages set by the murshid. Second, the implication of this Bai’at is an increase in confidence and deep knowledge in education. The recommendation from this study is the need for continuous training for educators to maximize the benefits of Bai’at in educational practice.